Já jako učitelka: profesní sebepojetí studentky učitelství v posledním ročníku pregraduální přípravy. / My teacher self: Professional self-concept of a student teacher in the last year of undergraduate training. - B.Pravdová (Czech Pedagogical Society, 2013)
The study describes the professional self-concept of a student teacher in the last year of undergraduate training. The study reflects overview studies dealing with the issue of self-concept and the professional self-concept of the teacher. The importance of positive professional self-concept at the onset of professionaldevelopment is documented and terms are conceptualized to suit needs of qualitative research. Content analysis of a free utterance and an in-depth interview concentrates on the search for dominating aspects of self-concept, the description of the selfconcept in relation to the self-discrepancy theory and the thoughts about a possibledevelopment of the professional self. It shows that the most significant aspect of the student's self-concept is the fear emanating from the discrepancy between the ideal self and the real self, between the ought self and the real self. Despite the factthat the student is formulating her self-concept as a teacher, it is constructed almost exclusively on experience gained in the role of a pupil. Following up this findings, the study discusses the question in what way the forming of professional self-concept should be influenced during the undergraduate teacher training.